2003
DOI: 10.1038/sj.emboj.7600015
|View full text |Cite
|
Sign up to set email alerts
|

The SNARE Ykt6 mediates protein palmitoylation during an early stage of homotypic vacuole fusion

Abstract: The NSF homolog Sec18 initiates fusion of yeast vacuoles by disassembling cis-SNARE complexes during priming. Sec18 is also required for palmitoylation of the fusion factor Vac8, although the acylation machinery has not been identified. Here we show that the SNARE Ykt6 mediates Vac8 palmitoylation and acts during a novel subreaction of vacuole fusion. This subreaction is controlled by a Sec17-independent function of Sec18. Our data indicate that Ykt6 presents Pal-CoA via its N-terminal longin domain to Vac8, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 69 publications
(139 reference statements)
6
82
1
Order By: Relevance
“…Antibodies to Ykt6 or the N-terminal longin domain interfered with palmitoylation at an early stage of fusion. Because in vitro palmitoylation required equimolar amounts of Ykt6 to modify Vac8, we suggested that acylation might occur by a nonenzymatic transfer mechanism (3,19). Such a mechanism has been suggested before and would explain previous autoacylation data (31).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Antibodies to Ykt6 or the N-terminal longin domain interfered with palmitoylation at an early stage of fusion. Because in vitro palmitoylation required equimolar amounts of Ykt6 to modify Vac8, we suggested that acylation might occur by a nonenzymatic transfer mechanism (3,19). Such a mechanism has been suggested before and would explain previous autoacylation data (31).…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies identified the SNARE Ykt6 as a factor that promotes Vac8 palmitoylation in vitro (19). Antibodies to Ykt6 or the N-terminal longin domain interfered with palmitoylation at an early stage of fusion.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In fact, the t-SNAREs syntaxins share a N-terminal H A H B H C domain necessary for viability and capable of intermolecular inhibition by binding to the Q-SNARE CCD (Nicholson et al, 1998;Parlati et al, 1999;Munson et al, 2000). Moreover, the v-SNAREs longins are characterized by the LD with profilin-like structure (Gonzalez et al, 2001;Tochio et al, 2001); this domain is capable to regulate membrane fusion (Martinez-Arca et al, 2000 and2001), as subcellular targeting (Hasegawa et al, 2003) by interacting with the clathrin adaptor AP-3 in the case of TI-VAMP/VAMP7 (Martinez-Arca et al, 2003), and protein palmitoylation in the case of Ykt6p (Dietrich et al, 2004).…”
Section: Introductionmentioning
confidence: 99%